2014
DOI: 10.1152/ajpregu.00491.2013
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 receptor signaling is not required for reduced body weight after RYGB in rodents

Abstract: -Exaggerated GLP-1 and PYY secretion is thought to be a major mechanism in the reduced food intake and body weight after Roux-en-Y gastric bypass surgery. Here, we use complementary pharmacological and genetic loss-of-function approaches to test the role of increased signaling by these gut hormones in high-fat diet-induced obese rodents. Chronic brain infusion of a supramaximal dose of the selective GLP-1 receptor antagonist exendin-9 -39 into the lateral cerebral ventricle significantly increased food intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
116
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(133 citation statements)
references
References 68 publications
(93 reference statements)
12
116
0
2
Order By: Relevance
“…6 Lessons from rodent models Although data in humans and pigs support a role for GLP-1 in controlling glucose metabolism after RYGBP, experiments with knock-out animal models challenge the role of GLP-1 in the control of body weight and glucose after RYGBP or vertical sleeve gastrectomy (VSG). Berthoud et al 59 showed that obese GLP-1R-deficient mice lost the same amount of body weight and fat mass and maintained similarly lower body weight compared with wild-type mice after a RYGBP-like procedure. 59 GLP-1 levels are also enhanced after VSG in humans 60 and rodents, 61 and are thought to be a mediator of diabetes remission after this surgery.…”
Section: Diabetes Relapsementioning
confidence: 99%
See 1 more Smart Citation
“…6 Lessons from rodent models Although data in humans and pigs support a role for GLP-1 in controlling glucose metabolism after RYGBP, experiments with knock-out animal models challenge the role of GLP-1 in the control of body weight and glucose after RYGBP or vertical sleeve gastrectomy (VSG). Berthoud et al 59 showed that obese GLP-1R-deficient mice lost the same amount of body weight and fat mass and maintained similarly lower body weight compared with wild-type mice after a RYGBP-like procedure. 59 GLP-1 levels are also enhanced after VSG in humans 60 and rodents, 61 and are thought to be a mediator of diabetes remission after this surgery.…”
Section: Diabetes Relapsementioning
confidence: 99%
“…Berthoud et al 59 showed that obese GLP-1R-deficient mice lost the same amount of body weight and fat mass and maintained similarly lower body weight compared with wild-type mice after a RYGBP-like procedure. 59 GLP-1 levels are also enhanced after VSG in humans 60 and rodents, 61 and are thought to be a mediator of diabetes remission after this surgery. 62 However, VSG-operated GLP-1R-deficient mice respond similarly to wild-type controls in terms of body weight loss, improved glucose tolerance, food intake reduction, and altered food selection.…”
Section: Diabetes Relapsementioning
confidence: 99%
“…51 However, subsequent studies in rodents directly testing roles for each of these gut hormones in the beneficial effects of RYGB and sleeve gastrectomy were largely negative. Neither GLP-1 receptor deficiency nor ghrelin deficiency appreciably changed the effects of RYGB 17,52 or sleeve gastrectomy, 53,54 and neither GLP-1 receptor nor PYY/Y2 receptor blockade in the brain attenuated RYGB-induced body weight suppression 17 (but see Chandarana et al 55 for a different outcome). Although these studies do not lend much support for individual roles of these hormones, it is possible that they act synergistically.…”
Section: Potential Underlying Mechanisms For Change In Set Pointmentioning
confidence: 99%
“…Consistent with our findings, transient hyperphagia and weight gain was also observed in female rats with sleeve gastrectomy during pregnancy and lactation. 15 In our mouse RYGB model, 16,17 we used a different approach, in that we lowered pre-surgical body weight by calorie-restriction before RYGB surgery. After 12 weeks on high-fat diet, mice weighed about 35 g, 12 g of which was fat mass.…”
Section: Behavioral Evidence For Rygb-induced Change In Defended Bodymentioning
confidence: 99%
“…Many investigators have suggested that GLP-1 may play a role. However, in rat studies, blocking GLP-1 does not affect the response to RYGB (84). Peptide YY knockout mice do not significantly decrease body weight after bypass surgery (85), suggesting that the hormone has some role in RYGB benefits.…”
Section: Physiological Mechanisms and Effectiveness Of Bariatric Surgerymentioning
confidence: 99%